Hispidulin attenuates the social withdrawal in isolated disrupted‐in‐schizophrenia‐1 mutant and chronic phencyclidine‐treated mice - Mouri, Akihiro (Br J Pharmacol, 2020)
BACKGROUND AND PURPOSE: Hispidulin is a flavonoid isolated from Clerodendrum inerme that was found to inhibit intractable motor tics. Previously, we found that hispidulin attenuates hyperlocomotion and the disrupted prepulse inhibition induced by methamphetamine and N‐methyl‐d‐aspartate (NMDA) receptor antagonists, two phenotypes of schizophrenia resembling positive symptoms. Hispidulin can inhibit COMT, a dopamine‐metabolizing enzyme in the prefrontal cortex (PFC) that is important for social interaction. Here, we investigated whether hispidulin would affect social withdrawal, one of the negative symptoms of schizophrenia. EXPERIMENTAL APPROACH: We examined whether acute administration of hispidulin would attenuate social withdrawal in two mice models, juvenile isolated disrupted‐in‐schizophrenia‐1 mutant (mutDISC1) mice and chronic phencyclidine (PCP)‐treated naïve mice. KEY RESULTS: In chronic PCP‐treated mice, hispidulin (10 mg·kg(−1), i.p.) attenuated social withdrawal similar to that observed with dopamine D(1) receptor antagonist (SCH‐23390, 0.02 mg·kg(−1), i.p.) and was mimicked by the selective COMT inhibitor, OR‐486 (10 mg·kg(−1), i.p.). Hispidulin increased extracellular dopamine levels in the PFC of chronic PCP‐treated mice. In isolated mutDISC1 mice, hispidulin also reversed social withdrawal. In both models, intra‐PFC microinjection of a D(1) agonist (SKF‐81297: 10 nmol/mouse/bilateral) reversed the impairment of Ser(897)phosphorylation at the GluN1 subunit of NMDA receptors, suggesting the association between GluN1 Ser(897)‐phosphorylation and D(1) activation in the PFC exits in both models. CONCLUSIONS AND IMPLICATIONS: Hispidulin attenuated social withdrawal by activating D(1) receptors indirectly through elevated dopamine levels in the PFC by COMT inhibition. This nature of hispidulin suggests that it a potential novel therapeutic candidate for the treatment of negative symptoms in schizophrenia.